Queering the Badlands and the Darkness: Rane Arroyo's Springsteen Poems. (14th March 2016) - Sandlin, Betsy A.
Abstract : Chicago-born, gay Puerto Rican poet Rane Arroyo (1954–2010) wrote at least ten poems dealing with American icon Bruce Springsteen and his music. Arroyo strategically "queered" many of Springsteen's popular lyrics and common tropes—particularly cars, darkness, and fraternity. Arroyo's Springsteen poems served as a powerful critique of the masculinist and heterosexist discourse of classic rock music.